Service Delivery and Corruption in Public Services: How Does History Matter? - Pandey, Priyanka (2012)
This paper provides microlevel evidence of how past institutions impact present economic outcomes. It looks at the impact of colonial land tenure institutions on local governance and education outcomes in northern India. Outcomes are worse in villages that belong to areas with a history of concentration of power with the elites. Such areas continue to retain a greater political presence of socially and economically dominant classes. Future research should examine the success of policies that attempt to break such persistence through empowerment of nonelite groups.